Perception of square and park characteristics and physical activity practice among High School students - Arieli Dias; Caroline Brand; Vanilson Lemes; Anelise Gaya; Adroaldo Gaya (Revista Brasileira de Atividade Física e Saúde)
This study aimed to investigate the association between perception of square/park characteristics (infrastructure, conservation, esthetics, safety, distance from residence, and access) and physical activity among High School students of the public network. It is an association study with a quantitative approach and a random sample composed of 168 adolescents (40.3% of boys and 59.7% of girls), aged between 14 and 18 years, from 10 high schools located in the city of Passo Fundo, southern Brazil. Perception of square/park characteristics was assessed through six questions about the characteristics of the neighborhood where students live. Physical activity was measured by means of a question adopted in the Youth Risk Behavior Surveillance System. Data analysis was carried out through descriptive statistics, Pearson’s chi-square test and Poisson regression. The regression results showed that students who answered that the square/park is not far from their home had a prevalence ratio of 2.29 (CI: 1.25-8.56) times of being physically active. In the best model, adjusted for sex and socioeconomic level, the prevalence ratio increased to 2.82 (CI: 1.31-11.22). Therefore, the study showed that the perceived distance between the square/park and the adolescents’ home influences physical activity practice, and students who reported that the square/park was not far from their home were more likely to be physically active.